2009
DOI: 10.1038/sj.bjc.6605027
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk in hospitalised psoriasis patients: a follow-up study in Sweden

Abstract: We examined overall and specific cancer risks among Swedish subjects who had been hospitalised one or more times for psoriasis. A database was created by identifying such patients from the Swedish Hospital Discharge Register and linking them with the Cancer Registry. Follow-up of patients was carried out from the last hospitalisation through 2004. A total of 15 858 patients were hospitalised for psoriasis during 1965 -2004, of whom 1408 developed cancer, giving an overall standardised incidence ratios (SIRs) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
74
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 25 publications
9
74
2
Order By: Relevance
“…In agreement with previous studies [2,4,5,14], we also found an increased risk of Hodgkin lymphoma and skin cancer. Moreover, we found a persistent strong association between sarcoidosis and non-Hodgkin lymphoma, which has been less clearly described [2,4,5,15].…”
supporting
confidence: 93%
See 3 more Smart Citations
“…In agreement with previous studies [2,4,5,14], we also found an increased risk of Hodgkin lymphoma and skin cancer. Moreover, we found a persistent strong association between sarcoidosis and non-Hodgkin lymphoma, which has been less clearly described [2,4,5,15].…”
supporting
confidence: 93%
“…Our finding of an increased overall risk of cancer among sarcoidosis patients is in accordance with several previous studies using the general population as a comparison [2][3][4][5][6], while one study found no association when comparing sarcoidosis patients with other hospitalised patients [12].…”
supporting
confidence: 92%
See 2 more Smart Citations
“…Among the 12 studies analysing risk of lymphoma in psoriasis compared to controls, seven showed an association between total lymphoma, [28][29][30] Hodgkin lymphoma, 30,31 nonHodgkin lymphoma [31][32][33][34] and psoriasis. Two studies 30,34 specifically assessed the risk of skin lymphoma in psoriasis and found an increased risk of cutaneous T-cell lymphomas (CTCL) associated with psoriasis.…”
Section: Cancersmentioning
confidence: 99%